EVALUASI KEBUTUHAN RAMBU DI SUNGAI MUSI KOTA PALEMBANG - Setio Boedi Arianto; Dwi Heriwibowo (Jurnal Penelitian Transportasi Darat, 2014)
ABSTRACTWaterways traffic signs is navigation tools for waterways/in inland waters which displays symbols, letters, numbers, words and/or a combination of them, as guidance for waterways/in inland waters transport . The purpose of this study is to find out the need for traffic signs in the River of Musi Palembang City. A method of analysis used is descriptive qualitative and quantitative analysis. The results of the analysis, is there are 82 unit of the number of traffic sign requirement for Musi River, with are 20 units of prohibition signs, 22 units of mandatory signs, 16 units of the warning signs, and 24 units of instructions/guide. Current condition there are 53 unit traffic signs installed they are 14 units of prohibition signs, 12 units of mandatory signs , 8 units of warning signs by, 19 units of instructions/guide numbered.Therefore, there are still lack of 29 units of traffic signs need to be installed on Musi River, devided into the prohibition signs for 6 units, mandatory signs for 10 units, warning signs for 8 units, and instructions/guide signs for 5 units.ABSTRAKRambu sungai adalah salah satu alat perlengkapan perambuan di perairan daratan dalam bentuk tertentu yang memuat lambang, huruf, angka, kalimat dan/atau perpaduan di antaranya, yang digunakan dalam pelayaran di sungai dan danau. Tujuan penelitian ini adalah untuk mengetahui kebutuhan rambu di Sungai Musi Kota Palembang. Metode analisis yang digunakan adalah analisis deskriptif kualitatif dan kuantitatif, kesimpulan dari penelitian ini adalah jumlah kebutuhan rambu di Sungai Musi sebanyak 82 unit, dengan perincian 20 unit rambu larangan, 22 unit rambu wajib, 16 unit rambu peringatan, dan 24 unit rambu penuntun/petunjuk, sedangkan rambu yang terpasang berjumlah 53 unit, dengan perincian rambu larangan sebanyak 14 unit, rambu wajib berjumlah 12 unit, rambu peringatan sebanyak 8 unit, rambu penuntun/petunjuk berjumlah 19 unit. Oleh karena itu, jumlah kebutuhan rambu di Sungai Musi masih terdapat kekurangan 29 unit, dengan perincian rambu larangan kurang 6 unit, rambu wajib masih kurang 10 unit, rambu peringatan kurang 8 unit, dan rambu penuntun/petunjuk masih kurang 5 unit.